Uji Aktivitas Antibakteri Fungi Endofit Tanaman Kunyit (Curcuma longa Linn.) Terhadap Bakteri Salmonella typhi: Antibacterial Activity Test of Endophytic Fungi (Curcuma longa Linn.) Against Salmonella typhi - Clarista Nabillah; Hamtini Hamtini; Adipura Atmadja Egok (Journal of Health, 2026)
Background: Typhoid fever is a systemic infectious disease caused by Salmonella typhi and remains a public health problem due to its high incidence rate and the increasing antibiotic resistance. Objectives: This study aimed to determine the antibacterial activity of endophytic fungi isolated from turmeric (Curcuma longa Linn.) against Salmonella typhi. Methods: This study employed a descriptive exploratory research design, involving the isolation of endophytic fungi from the leaves, stems, and rhizomes of turmeric plants using Potato Dextrose Agar (PDA) supplemented with chloramphenicol, followed by the identification of the isolates based on their macroscopic and microscopic characteristics. Furthermore, antibacterial activity was evaluated using the diffusion method on Mueller Hinton Agar (MHA). Results: Four endophytic fungal isolates were obtained, consisting of three isolates from the stem (B1, B2, and B3) and one isolate from the rhizome (R). Isolates B1 and B2 were identified as Acremonium sp., B3 as Mucor sp., and R as Aspergillus sp. Antibacterial activity testing against Salmonella typhi showed that all isolates exhibited very strong activity. The mean inhibition zone diameters were 29 mm for isolates B1 and B2, 27 mm for isolate B3, and 22 mm for isolate R. Meanwhile, the positive control using chloramphenicol discs showed an inhibition zone diameter of 30.5 mm. Conclusions: This study provides data on the diversity of endophytic fungi successfully cultured from various parts of the turmeric plant and demonstrates strong antibacterial activity against Salmonella typhi, thereby contributing to the enrichment of scientific knowledge regarding the potential of endophytic fungi as alternative sources of antimicrobial agents.